2019
DOI: 10.31925/farmacia.2019.5.19
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Profile and Antioxidant Activity of Almond Oils Obtained From Six Romanian Varieties

Abstract: The almond nuts are an important source of unsaturated fats that may contribute to a significant decreasing of cholesterol level in blood. Six patented almond varieties grown in North-Western part of Romania, Bihor County (Sort A, Sort B, Sort C, Sort D, Sort E, and Sort F) were selected in order to determine the fatty acid composition and the antioxidant capacity of the oils obtained from almonds. Four fatty acids (stearic, palmitic, oleic and linoleic) were determined through their methylated derivatives by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 23 publications
2
14
3
2
Order By: Relevance
“…The antioxidant activity of the samples was determined using radical scavenging DPPH (1,1-diphenyl-2-picrylhydrazyl) free assay, as earlier reported 24 . The data obtained revealed that for the S. hortensis essential oil (SHEO), the inhibition is 80.02 ± 0.24%, while for the heated essential oil sample (SHEO190-2.5), inhibition was 87.73 ± 0.08%.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activity of the samples was determined using radical scavenging DPPH (1,1-diphenyl-2-picrylhydrazyl) free assay, as earlier reported 24 . The data obtained revealed that for the S. hortensis essential oil (SHEO), the inhibition is 80.02 ± 0.24%, while for the heated essential oil sample (SHEO190-2.5), inhibition was 87.73 ± 0.08%.…”
Section: Resultsmentioning
confidence: 99%
“…As a reference, positive controls containing 2.5–50 mg L −1 gallic acid were prepared. All of the experiments were conducted in triplicate, and the results were expressed as % inhibition (calculated as in [ 65 ]) and mg gallic acid equivalent L −1 (GAE L −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The antioxidant capacity of the LEOs was evaluated by using the DPPH assay, as reported earlier [ 63 ]. A total of 0.1 mL sample was mixed with 3 mL of 0.2 mm ethanolic DPPH• solution.…”
Section: Methodsmentioning
confidence: 99%